If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5 = -13 + 4x Reorder the terms: 5 + 2x = -13 + 4x Solving 5 + 2x = -13 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5 + 2x + -4x = -13 + 4x + -4x Combine like terms: 2x + -4x = -2x 5 + -2x = -13 + 4x + -4x Combine like terms: 4x + -4x = 0 5 + -2x = -13 + 0 5 + -2x = -13 Add '-5' to each side of the equation. 5 + -5 + -2x = -13 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = -13 + -5 -2x = -13 + -5 Combine like terms: -13 + -5 = -18 -2x = -18 Divide each side by '-2'. x = 9 Simplifying x = 9
| -12x-57=132-3x | | 2+x+4=12 | | 3p-6=10-2m | | -12x-12=-11x+9 | | -4x=0.8 | | N/2-9=-9 | | -31+x=4x+20 | | -4+10+6x=28 | | -12+8x=6x+28 | | 3/6=g/90 | | 6n^2-45n+84=0 | | -5x-39=57+x | | -18p=-9 | | xx+1=0 | | 4lnx=60 | | -34+9x=6x+53 | | -4=-16x | | 7/8=n | | -29-10x=-12x+25 | | 37=5p-3 | | -152-x=8x+55 | | 10x+19=3x+229 | | 10x+19=3x+22 | | -82-12x=-5x+65 | | 48=4n+20 | | x+6=4x^2-12x+9 | | -101-3x=-10x+39 | | -95+12x=6x+31 | | Y^2=14y-48 | | =2x+2 | | -39+6x=10x+17 | | 47=5m+2 |